Non-netralitas kebijakan moneter: Pengujian atas pandangan ekonomi makro klasik baru - Munkhorim Misanam (Economic Journal of Emerging Markets, 1997)
Rational Expectation (Ratex) Hypothesis has been widely spread, even became the foundation of Neo Classic though. But the validity of this hypothesis is still being debated. Since the hypothesis has a serious implication, in neutrality of economic policy, more investigation is important to do. This article evaluates whether the hypothesis is contextual to Indonesian economy or not. By taking note of the last development of the model and using two different money scale, i.e. Ml and M2, it finds an indication that rationality and neutrality are not shown in Indonesian economy, it means monetary policy has an effect on real variable in the economy.